Matthew Krishanu - Griffiths, Georgia; Price, Matt (Anomie, 2023)
Matthew Krishanu's paintings explore topics including childhood, race, religion, art history, family, grief and love. His subjects, frequently Brown people, are realised with a shallow pictorial depth, delicate washes of colour, and with a sense of interior life. Through this, Krishanu questions the positions of his painterly subjects and depictions of landscapes in relation to the legacy of European colonialism and the art historical canon. Krishanu's practice is heavily informed by his early childhood spent in Dhaka where his parents moved in order to work for the Church of Bangladesh.0This, his first trade monograph, presents a number of series of Krishanu?s works: Another Country, Expatriates, Mission, House of God, Religious Workers and In Sickness and In Health. The publication features essays by Mark Rappolt and Dorothy Price, alongside an interview with the artist by Ben Luke. Rappolt, Editor-in-Chief at ArtReview magazine, details the various worlds present within Krishanu's paintings. He draws out key themes within Krishanu's oeuvre such as power, religion, identity and memory. Price, Professor of Modern and Contemporary Art and Visual Culture at The Courtauld, writes sensitively about solitude, memory and emotion which are palpable within Krishanu?s work. In particular, the series In Sickness and In Health, which traces a life path of Uschi Gatward, the artist's late wife, over sixteen years to her untimely death from cancer in late 2021. In an interview with Luke, a critic and editor at The Art Newspaper, Krishanu discusses his practice in relation to ideas of religion, race, global art history, photography, health and personal experiences. Krishanu's work explores, in the artist's own words, the puzzle of painting. Produced by Anomie Publishing and Niru Ratnam, London, the publication has been supported by Guy Halamish; Jhaveri Contemporary, Mumbai; Niru Ratnam, London; Taimur Hassan; and Tanya Leighton, Berlin and Los Angeles
Keywords: Krishanu, Matthew -- 1963-; Malerei; Krishanu, Matthew / 1980-; Bildband